On sufficient condition of ergodicity of volterra quadratic operators of bisexual population - Ganikhodjaev, Nasir; Jamilov, Uygun (Insitute of Mathematics of Uzbekistan, 2014)
We consider the set of all Volterra quadratic operators of bisexual population with three values of alleles. We show that this set is convex and describe the extreme points of this set.